2012
DOI: 10.1021/nn300928g
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of a Zwitterionic Tantalum Oxide Nanoparticle X-ray Contrast Agent

Abstract: Tantalum oxide nanoparticles show great potential as the next generation of X-ray contrast media. Recently, we reported advances in tantalum oxide nanoparticles and identified improvements that were required for such particles to progress further. Namely, the viscosity of concentrated particles, the amount of retention in reticuloendothelial (RES) tissues, and the effect of large quantities of particles on the kidneys after administration were all identified as critical factors which needed further study, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 41 publications
1
70
0
Order By: Relevance
“…These important considerations are beyond the scope of tantalum clearly merits further consideration. Results published to date suggest that some tantalum oxide nanoparticles have physicochemical and biological characteristics that make them attractive for use as intravascular CT contrast agents (16,19,21,22). These water-soluble agents can be formulated at concentrations required for CT and radiography and are well tolerated at high doses.…”
Section: Contrast Media: Ct Image Contrast Of High-z Elements: Phantomentioning
confidence: 99%
“…These important considerations are beyond the scope of tantalum clearly merits further consideration. Results published to date suggest that some tantalum oxide nanoparticles have physicochemical and biological characteristics that make them attractive for use as intravascular CT contrast agents (16,19,21,22). These water-soluble agents can be formulated at concentrations required for CT and radiography and are well tolerated at high doses.…”
Section: Contrast Media: Ct Image Contrast Of High-z Elements: Phantomentioning
confidence: 99%
“…[ 135 ] Moreover, this research demonstrated that the mixed-charge zwitterionic surfaces on NPs can also be constructed from other types of ligands besides alkanethiols. So it promises to surface modify various types of NPs with mixed-charge monolayers by using the corresponding ligands that have end groups can conjugate with NPs.…”
Section: Stabilization Of Nps With Mixed-charge Monolayersmentioning
confidence: 83%
“…Previously, a assessment of zwitterionic tantalum oxide nanoparticles in vivo showed that the small 5 nm mixed-charge siloxanes coated nanoparticles have much lower retention in liver, spleen and kidney than the non-zwitterionic diethylphosphatoethyl-derivatized siloxane coated nanoparticles. [ 135 ] What's more, these tantalum oxide nanoparticles with the mixed-charge zwitterionic coating did not induce pathological responses in the kidneys due to effi cient renal clearance, which makes them very promising as novel X-ray contrast media. Importantly, the mixed-charge AuNPs showed higher accumulation and slower clearance in tumors than PEGylated AuNPs do for times of 24-72 h (Figure 7 D).…”
Section: Nonfouling Mixed-charge Nps In Vitro and In Vivomentioning
confidence: 99%
“…26 Preclinical murine data has shown superior imaging performance, encouraging physicochemical properties, and low retention levels. 22,24 Although the biological properties of tungsten are less well understood, tungsten agents have also been identified as potential CT contrast agents and were used in preclinical DECT imaging. 23,32 Other high-Z elements with potential as possible CT contrast agents include gold, 33,34 ytterbium, 35 and gadolinium.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to evaluate a representative selection (Table 1) of conventional and novel CT contrast elements either in development [22][23][24][25] or in routine clinical use. The nearthreefold difference in k edge energy between different elements was anticipated to result in widely varying attenuation profiles over the 40 to 140 keV range.…”
Section: Introductionmentioning
confidence: 99%